2013
DOI: 10.5114/wo.2013.34623
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node in thyroid tumors – own experience

Abstract: Aim of the studyTo determine the feasibility of sentinel lymph node biopsy (SLNB) for the evaluation of the cervical lymph node status in patients with thyroid tumors.Material and methodsTwenty-three patients with suspected thyroid cancer were enrolled in the study. 0.5–1.0 ml of 1% Patent Blue dye was injected intratumorally. After SLNB, thyroidectomy and proper lymphadenectomy were performed.ResultsSentinel lymph node was detected in 20 (86.9%) patients. Thirty-one SLNs were found – 21 (67.7%) were located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A lower detection rate using the blue dye technique compared to the radiotracer has been reported in other malignancies (including thyroid cancer) too [15,27]. Considering the adverse reactions associated with blue dyes [28] and possible staining of parathyroid glands by blue dye [22,29], our results suggest that a radiotracer only technique would be sufficient for sentinel node mapping in thyroid cancer patients.…”
Section: Discussionmentioning
confidence: 80%
“…A lower detection rate using the blue dye technique compared to the radiotracer has been reported in other malignancies (including thyroid cancer) too [15,27]. Considering the adverse reactions associated with blue dyes [28] and possible staining of parathyroid glands by blue dye [22,29], our results suggest that a radiotracer only technique would be sufficient for sentinel node mapping in thyroid cancer patients.…”
Section: Discussionmentioning
confidence: 80%
“…Generally, the recommended treatment is total thyroidectomy with lymph node dissection, followed by radiotherapy [ 24 ]. Many clinicians offer sentinel and other lymph node biopsies for suspected differentiated thyroid cancer [ 25 ] to avoid unnecessary lymph node dissection. However, the entire SCC group had a 55% chance of a lymph node metastasis diagnosis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…SLN detection rate in patients was 83.1% in the first group, 98.8% in the second group and 97.8% in the third group. In two studies of the third group, Catarci have shown better result of detection with radiocolloid relative to the vital dye (83.3% versus 50%), while Lee showed a better IR with vital dye (93% versus 88.4%) (24,25,26).…”
Section: Sentinel Node Detection In Patients With Thyroid Carcinoma: mentioning
confidence: 93%